2020
DOI: 10.1038/s41467-020-19517-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of methane to formaldehyde and CO on B2O3 catalysts

Abstract: Direct oxidation of methane to value-added C1 chemicals (e.g. HCHO and CO) provides a promising way to utilize natural gas sources under relatively mild conditions. Such conversions remain, however, a key selectivity challenge, resulting from the facile formation of undesired fully-oxidized CO2. Here we show that B2O3-based catalysts are selective in the direct conversion of methane to HCHO and CO (~94% selectivity with a HCHO/CO ratio of ~1 at 6% conversion) and highly stable (over 100 hour time-on-stream ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 45 publications
4
63
0
Order By: Relevance
“…S5† also confirm that no characteristic crystal plane of B 2 O 3 could be observed in PBN@Al 2 O 3 (N). Therefore, we synthesized the B 2 O 3 @Al 2 O 3 (N) catalyst the same as the control catalyst according to the literature, 42–44 while the detailed comparison is not included here (Fig. S6†).…”
Section: Resultsmentioning
confidence: 99%
“…S5† also confirm that no characteristic crystal plane of B 2 O 3 could be observed in PBN@Al 2 O 3 (N). Therefore, we synthesized the B 2 O 3 @Al 2 O 3 (N) catalyst the same as the control catalyst according to the literature, 42–44 while the detailed comparison is not included here (Fig. S6†).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that non-metallic boron-based catalysts exhibit outstanding catalytic performance in dehydrogenation [145,146]. Based on this finding, Tian et al [36] reported that B 2 O 3 catalysts were highly stable and selective for the partial oxidation of methane to HCHO and CO. The mechanism of methane activation on a B 2 O 3 surface adequately explains the generation process of HCHO and CO, as shown in Figure 10, which reveals that molecular O 2 is bound to the electron-deficient B centers on the B 2 O 3 surfaces which are moderate oxidants accounting for methane activation and suppress the formation of CO 2 .…”
Section: Other Catalystsmentioning
confidence: 99%
“…Since the transition metal Mo can have various oxidation states, it can create a redox cycle between high and low oxidation states. This is required in the Mars-Van Krevelen mechanism, which has been proposed for the selective oxidation of olefins to oxygenates [32][33][34][35][36]. Recent studies have indicated that peroxide species produced by the activation of O 2 on isolated reduced Mo(IV), rather than lattice oxygen are the active species for methane oxidation [37,38].…”
Section: Catalytic Gas-phase Partial Oxidation Of Methane Into Formal...mentioning
confidence: 99%
“…Methane is an abundant and readily accessible feedstock 34 for the production of various valuable liquid chemicals, such as oxygenated [35][36][37][38][39][40][41][42] or aromatic compounds. [43][44][45][46][47] Zn-Modified zeolites are promising catalysts for the activation and conversion of light alkanes.…”
Section: Introductionmentioning
confidence: 99%